2011
DOI: 10.1007/s11104-011-0870-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochar adsorbed ammonia is bioavailable

Abstract: Biochar is produced as a by-product of the low temperature pyrolysis of biomass during bioenergy extraction and its incorporation into soil is of global interest as a potential carbon sequestration tool. Biochar influences soil nitrogen transformations and its capacity to take up ammonia is well recognized. Anthropogenic emissions of ammonia need to be mitigated due to negative environmental impacts and economic losses. Here we use an isotope of nitrogen to show that ammonia-N adsorbed by biochar is stable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(189 citation statements)
references
References 34 publications
14
160
2
8
Order By: Relevance
“…Hale, et al [10] who studied the adsorption of ammonium by biochars prepared from corn cob and cacao shell suggested that ammonium is weakly adsorbed on the surface of the biochar through electrostatic exchanges with other cationic species. This is consistent with the findings of Taghizadeh-Toosi, et al [11] who reported that ammonium adsorbed by biochar was readily available to plants. Upon close inspection of the results, a trend was observed which indicated that the addition of biochar may enhance the NH4 + removal efficiency overtime.…”
Section: Ammonium Removalsupporting
confidence: 93%
“…Hale, et al [10] who studied the adsorption of ammonium by biochars prepared from corn cob and cacao shell suggested that ammonium is weakly adsorbed on the surface of the biochar through electrostatic exchanges with other cationic species. This is consistent with the findings of Taghizadeh-Toosi, et al [11] who reported that ammonium adsorbed by biochar was readily available to plants. Upon close inspection of the results, a trend was observed which indicated that the addition of biochar may enhance the NH4 + removal efficiency overtime.…”
Section: Ammonium Removalsupporting
confidence: 93%
“…The treatment of 50 kg N¨ha´1 combined with BC benefited the crop yield similar to that in 100 kg N¨ha´1 applied alone treatment. This could be due to the ability of BC to reduce urea N losses through reduction of leaching or gaseous losses [36].…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, biochar in the soil can retain N which is released from microbes (Müller et al 2002, Groffman et al 2006) and/or roots (Fitzhugh et al 2001) dying due to the frost and, thus, inhibit the formation of N 2 O. Taghizadeh-Toosi et al (2011) stated that N adsorbed by biochar is bioavailable, but the results of this study do not fully support the statement. Our results indicate that biochar retains, at least temporarily, both NH 4 + and NO 3 -in the soil (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…In this study, the used biochar was made from spruce chips under rather low temperatures (400-450°C). Some earlier studies have found that wood-originated biochar can absorb N (Taghizadeh-Toosi et al 2011, Dempster et al 2012) and increase the amounts of inorganic and organic N in the soil (Clough et al 2010, Biederman and Harpole 2013, Güereña et al 2013 but N is available for plants (Taghizadeh-Toosi et al 2011) and microbes (Dempster et al 2012). Our results, however, show that the wood-originated aged biochar characterized by a moderate specific surface area (209.7 m 2 g -1 ) can retain N and thus diminish N 2 O flux and leaching of NH 4 + and NO 3 -during FT. Our results are supported by Singh et al (2010), who stated that according to their experiment, which lasted over 5 months, the effectiveness of biochar in reducing N 2 O emissions and NH 4 + leaching increased with the ageing of biochar in the soil.…”
Section: Resultsmentioning
confidence: 99%